Does maternal consumption of nutritive and non-nutritive sweeteners result in offspring hypertension? - You-Lin Tain; You-Lin Tain; You-Lin Tain; Chien-Ning Hsu; Chien-Ning Hsu (Frontiers in Nutrition)
The consumption of nutritive and non-nutritive sweeteners (NNS) has increased significantly in recent decades. The nutritional status of pregnant women plays a crucial role in determining the likelihood of their offspring developing hypertension in adulthood. While NNSs provide a sweet taste without adding to sugar intake, emerging evidence suggests that maternal consumption of not only nutritive sweeteners (such as fructose) but also NNS may lead to adverse outcomes in offspring, including hypertension. This review provides an overview of the latest research connecting maternal intake of sweeteners to the long-term risk of hypertension in offspring. We examine proposed mechanisms underlying the programming of offspring hypertension by sweeteners, encompassing oxidative stress, dysregulated nutrient sensing signals, abnormal renin-angiotensin system, transcriptome changes, and dysbiotic gut microbiota. Additionally, we outline preventive strategies that can help alleviate offspring hypertension programmed by maternal diets high in sweeteners. Recent advancements in understanding the mechanisms through which maternal consumption of nutritive and non-nutritive sweeteners contributes to offspring hypertension offer promise for addressing this widespread health concern at its developmental roots. Nonetheless, further research is needed to educate the public about the safety of sweetener consumption during pregnancy and lactation.